PENGARUH PENERAPAN STRATEGI PQ4R BERBASIS HIERARKI KONSEP TERHADAP HASIL BELAJAR SISWA PADA POKOK BAHASAN STOIKIOMETRI - rizki yustika; elvi yenti (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
AbstractThe research is an experimental research, motivated by the results of studying chemistry Pharmacy Vocational High School students Ikasari Pekanbaru which is still low with an average value below the Minimum Learning Mastery Standard (KKM) and lack of interest of students reading chemistry books.The aim of the study is to improve students’ learning outcomes on the subject in the 10th grade Stoichiometry. The samples in this study were taken from two classes of the X5 as experimental class and class X4 as the control class. The sample is selected by using simple random sampling. Data collection techniques in this research are used to test the homogeneity as preliminary data on previous material, documentation, observation, pretest and posttest as the final data. To determine whether or not a sample is homogeneous, the analysis employs Bartlet test, and to end the data the